The Effect of E-Service Quality on E-Loyalty Mediated by E-Satisfaction of Draiv Food Customers in Morowali Regency - Mohammad Zeylo Auriza; Agung Winoto; Sri Wanti; Citra Antasari; Nurnadila; Sasmita Kasim (Jurnal Sinar Manajemen, 2024)
Online transport has experienced rapid growth in the digital age, changing the way people travel. These services are provided through digital platforms such as online taxis or ride-hailing, which have become the first choice for many customers. In Indonesia, the online transport sector is growing rapidly and has become a daily necessity for consumers. Platforms such as online taxis and online motorbike taxis have been present in various regions, including Morowali Regency in Central Sulawesi. Draiv Company is one of the popular ride-hailing applications in the area. Web-based services are also widely used in online transport, with the concept of relational marketing to maintain customer loyalty. Online service quality has a positive effect on customer satisfaction and e-loyalty. Customer e-satisfaction occurs when the performance of the services offered meets or even exceeds customer expectations, which in turn increases customer commitment.